RYR2 deficient human model identifies calcium handling and metabolic dysfunction impacting pharmacological responses - Starnes, Linda; Hall, Andrew; Etal, Damla; Cavallo, Anna-Lina; Grabowski, Piotr; Gallon, John; Kha, Michelle; Hicks, Ryan; Pointon, Amy (Frontiers in Cardiovascular Medicine, 2024)
Creation of disease models utilizing hiPSCs in combination with CRISPR/Cas9 gene editing enable mechanistic insights into differential pharmacological responses. This allows translation of efficacy and safety findings from a healthy to a diseased state and provides a means to predict clinical outcome sooner during drug discovery. Calcium handling disturbances including reduced expression levels of the type 2 ryanodine receptor (RYR2) are linked to cardiac dysfunction; here we have created a RYR2 deficient human cardiomyocyte model that mimics some aspects of heart failure. RYR2 deficient cardiomyocytes show differential pharmacological responses to L-type channel calcium inhibitors. Phenotypic and proteomic characterization reveal novel molecular insights with altered expression of structural proteins including CSRP3, SLMAP, and metabolic changes including upregulation of the pentose phosphate pathway and increased sensitivity to redox alterations. This genetically engineered in vitro cardiovascular model of RYR2 deficiency supports the study of pharmacological responses in the context of calcium handling and metabolic dysfunction enabling translation of drug responses from healthy to perturbed cellular states.